1998
DOI: 10.1046/j.1469-8137.1998.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and C allocation of Populus tremuloides genotypes in response to atmospheric CO2 and soil N availability

Abstract: We grew cuttings of two early (mid Oct.) and two late (early Nov.) leaf-fall Populus tremuloides Michx. genotypes (referred to as genotype pairs) for c. 150 d in open-top chambers to understand how twice-ambient (elevated) CO # and soil N availability would affect growth and C allocation. For the study, we selected genotypes differing in leaf area duration to find out if late-season photosynthesis influenced C allocation to roots. Both elevated CO # and high soil N availability significantly increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 44 publications
13
69
0
4
Order By: Relevance
“…A number of other studies on trees have found that CO 2 -induced increases in fine-root standing crop were limited at lower levels of N availability (Curtis and Wang 1998;Kubiske et al 1998;Pregitzer et al 2000;Prior et al 1997;Zak et al 2000), presumably reflecting resource limitations for increased growth. Conversely, Dyckmans and Flessa (2002) and Liu et al (2002) reported that C allocation to beech and spruce roots increased in response to CO 2 enrichment only at low levels of N. Dyckmans and Flessa (2002) concluded this showed a tendency for the plant to increase soil N uptake to match the elevated C supply as predicted by tree models (Lacointe 2000).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of other studies on trees have found that CO 2 -induced increases in fine-root standing crop were limited at lower levels of N availability (Curtis and Wang 1998;Kubiske et al 1998;Pregitzer et al 2000;Prior et al 1997;Zak et al 2000), presumably reflecting resource limitations for increased growth. Conversely, Dyckmans and Flessa (2002) and Liu et al (2002) reported that C allocation to beech and spruce roots increased in response to CO 2 enrichment only at low levels of N. Dyckmans and Flessa (2002) concluded this showed a tendency for the plant to increase soil N uptake to match the elevated C supply as predicted by tree models (Lacointe 2000).…”
Section: Resultsmentioning
confidence: 96%
“…Belowground, N availability has been observed to curtail CO 2 -induced increases in root standing crop, production, and/or mortality in both trees (Curtis and Wang 1998;Kubiske et al 1998;Pregitzer et al 2000;Prior et al 1997;Zak et al 2000) and grasses (Kettunen et al 2005;Li et al 2004;Loiseau and Soussana 1999).…”
Section: Introductionmentioning
confidence: 96%
“…While these increases in fine root standing stock represent increased levels of R A , they also facilitate increases in R H . For the 1999 data, King et al (2001) reported a 139% increase in dead-root stock under elevated CO 2 , and the authors have concluded that elevated atmospheric CO 2 increases fine root turnover (Kubiske et al 1998;Pregitzer et al 1995Pregitzer et al , 2000. As most microbial communities are C limited , this enhanced addition of organic matter through organic acids, root turnover, and increased microbial metabolism likely increased R H as well .…”
Section: Discussionmentioning
confidence: 93%
“…6). Previous reports also show a positive response of RLD or root biomass to fertilization (Johnson 1990;Kubiske et al 1998;Majdi 2001;Pregitzer et al 2000). However, the influence of resources on root system expansion was small in comparison to the effect of temporal, spatial or genetic factors (Tables 4 and 5), and the magnitude of the response to resource availability was dependent upon the level of other factors (Figs.…”
Section: Resource Availabilitymentioning
confidence: 85%